Multi-Skin Adaptive Ventilated Facade: A Review - Darya Andreeva; Darya Nemova; Evgeny Kotov (Energies, 2022)
Multi-skin ventilated facades with integrated building elements that respond to climatic conditions (mechanized openings and automatic shading with intelligent control) present the potential of improving overall annual energy savings by adapting the thermal properties of buildings. This paper presents a literature review on multi-skin adaptive ventilated facades. Additionally, this article presents a literature review on building envelopes that contain inner-air layers. The operation modes of the air layer used in building enclosure structures are classified and summarized and the thermal performance and benefits of climate-adaptive facades are discussed and reviewed. The existing operation modes of the air layer used in building envelopes are summarized, outlined and roughly classified into the following types: the enclosed type, the naturally ventilated type and the mechanically ventilated type. One of the sustainable development trends is the investigation and application of energy-efficient climate-adaptive facades. In this study, the energy modeling of a high-rise office building was calculated using the Green Building Studio. The annual energy, the annual CO2 emissions, and life cycle energy for the following three types of facade were estimated: a single-layer facade made of three-layer glass with argon, a double ventilated facade, and a triple ventilated facade with a double chamber. The calculation results show that the annual energy of the building with an adaptive triple-skin facade could be reduced by 15% compared with buildings with a single skin facade.